PENGARUH CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER) DAN UKURAN PERUSAHAAN TERHADAP RETURN ON EQUITY (ROE) PADA PT MUSTIKA RATU TBK PERIODE 2013-2022 - Qurrotu Ainii, Fitri; Nofiana, Lina (Journal of Research and Publication Innovation, 2024)
This study aims to determine how the effect of Current Ratio (CR), Debt to Equity Ratio (DER) and Company Size both partially and simultaneously on Return On Equity (ROE) at PT Mustika Ratu Tbk for the 2013-2022 Period. The data used in this study are secondary. Using descriptive research methods and the data is quantitative. The population used is the entire annual financial report of PT Mustika Ratu Tbk. The samples used in this study are in the form of financial position reports and profit / loss statements. The analysis method used in this research is descriptive test, classical asumi test, linear regression test and hypothesis testing using SPSS version 27. The research results for Current Ratio (CR) show that partially it has a significant and positive effect on Return On Equity (ROE). This is evidenced by the tcount value of 3.556 < t table 2.447 with a significant value of 0.012 < 0.05. The research results for Debt to Equity Ratio (DER) show that partially it has a significant and negative effect on Return On Equity (ROE). This is evidenced by the tcount of -6.811 > t table 2.447 with a significant value of 0.000 < 0.05. The research results for Company Size show that partially it has a significant and positive effect on Return On Equity (ROE). This is evidenced by the tcount value of 17.837 > t table 2.447 with a significant value of 0.000 < 0.05. Simultaneously CR, DER, and Company Size have a significant effect on ROE at PT Mustika Ratu Tbk. Period 2013-2022. This is evidenced by the fcount of 155.862 > ftabel 4.35 with a significant value of 0.000 < 0.05.